2020
DOI: 10.1002/cam4.3050
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum erythropoietin levels and renal reversibility in patients with renal impairment from multiple myeloma

Abstract: Renal impairment (RI) is a common clinical presentation in patients with multiple myeloma (MM). Despite treatment with novel agents or management strategies that focus on the disease response, some patients develop irreversible RI. This study aimed to determine the influencing, clinical variables of renal reversibility in patients with RI treated with novel drugs. We analyzed 244 patients newly diagnosed with MM retrospectively. Maximum renal response was assessed according to the criteria for the definition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
2
Order By: Relevance
“…However, the relationship between alterations in serum albumin levels and reversibility of renal function is not well understood. Some studies suggest that serum albumin levels are not associated with renal reversibility in MM [22,23]. In contrast, our preliminary clinical data showed that serum albumin was higher in the non-reversible group compared to the reversible group.…”
Section: Introductioncontrasting
confidence: 83%
See 2 more Smart Citations
“…However, the relationship between alterations in serum albumin levels and reversibility of renal function is not well understood. Some studies suggest that serum albumin levels are not associated with renal reversibility in MM [22,23]. In contrast, our preliminary clinical data showed that serum albumin was higher in the non-reversible group compared to the reversible group.…”
Section: Introductioncontrasting
confidence: 83%
“…However, the predictive value of changes in serum albumin for renal reversibility has not been fully elucidated. Some studies have suggested that serum albumin levels are not associated with renal reversibility [22,23]. In our study, by comparing data from the reversible and non-reversible groups of newly diagnosed myeloma patients, we unexpectedly found that level of serum albumin was actually higher in the non-reversible group than that in the reversible group, suggesting that elevated serum albumin levels in these MM patients are associated with decreased residual renal function.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation